2011
DOI: 10.1111/j.1750-3841.2011.02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Consumer Acceptability and Sensory Characteristics for Marinated Broiler Breast Meat

Abstract: In the present study, the effects of marination on the quality of poultry breast meat deboned at various times postmortem (PM) were investigated. One of the specific goals was to optimize the processing conditions between deboning time, tumbling duration, and poultry breast meat tenderness, with the objective of developing specific recommendations on processing practices adopted by the poultry industry. Broiler breast (Pectoralis major) muscles deboned at 0.25, 1.5, 3, 6, and 24 h PM were vacuum tumbled with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…; Lee et al . ). Lyon and Lyon () investigated sensory texture profile of broiler breast meat as influenced by PM deboning time and cooking method (MW [microwave] versus WC methods) and reported that initial hardness was not significantly affected by cooking method although the mean sensory score for the WC method was slightly higher than that for the MW method.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Lee et al . ). Lyon and Lyon () investigated sensory texture profile of broiler breast meat as influenced by PM deboning time and cooking method (MW [microwave] versus WC methods) and reported that initial hardness was not significantly affected by cooking method although the mean sensory score for the WC method was slightly higher than that for the MW method.…”
Section: Resultsmentioning
confidence: 97%
“…; Lee et al . ). Therefore, there were 18 combinations of the deboning time and cooking method in this full factorial treatment design.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…In our study, 20 min was used for marination duration, which is much longer than 4 min. Lee et al (2011) found that marinade retention in the fillets marinated for 30 min was consistently higher than those for 15 min. These results suggest that in addition to meat WHC, other factors, such as meat surface conditions, the depth of marinade penetration in meat, or both, can also significantly affect marinade retention (Heath and Owens, 1991).…”
Section: Resultsmentioning
confidence: 88%